A technical guide to IPSec virtual private networks - Tiller, James S. (CRC Press, 2001)
"Starting with a primer on the IP protocol suite, the book travels layer by layer through the protocols and the technologies that make VPNs possible. It includes security theory, cryptography, authentication, IKE, IPSec, encapsulation, keys, and policies. After explaining the technologies and their interrelationships, the book provides sections on implementation and product evaluation. A Technical Guide to IPSec Virtual Private Networks arms information security, network, and system engineers and administrators with the knowledge and the methodologies to design and deploy VPNs in the real world for real companies."--Jacket